An Analysis of English Language Exposure at Home and Its Perceived Impact on Young Children - Restu Dessy Maulida (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates the forms of English language exposure provided by parents at home, parents’ perceptions of its impact on young children’s English development, and the challenges they face in an English as a Foreign Language (EFL) context. Using a qualitative descriptive design, data were collected through an online questionnaire distributed to 18 parents of children aged 4–6 years. The data were analyzed using descriptive statistics for closed-ended questions and thematic analysis for open-ended responses. The findings reveal that English exposure at home is primarily delivered through multimodal activities, including watching videos, singing songs, reading storybooks, and engaging in simple conversations, with digital media especially YouTube as the dominant source. Most parents reported observing positive developments in their children’s English abilities, particularly in vocabulary recognition, pronunciation imitation, passive comprehension, and increased interest in English content. However, several challenges were identified, including parents’ limited English proficiency, time constraints, children’s fluctuating interest, and difficulties in selecting appropriate learning materials. These findings highlight the important role of the home environment in supporting early second language acquisition, particularly through informal and interaction-based exposure. The study contributes to the understanding of how home literacy environments function in EFL contexts and emphasizes the need for supporting parents in providing effective English exposure at home.